Language Structure with “Past Participle + Verb” in Grabar - Poghosyan, Norayr (Bulletin of Yerevan University B: Philology, 2022)
Using numerous examples taken from the works of the Grabar, we made an attempt to identify and consider the morphological and stylistic aspects of the construction “past participle + verb” (PPV). This is a unique linguistic unit of the Old Armenian language, and the author of this article has made an attempt to define this structure, based on the actual material of the texts. PPV is one of the stylistically rich means of expressiveness of the ancient Armenian language, used in all works and by all authors. The author of this article has also compared how different philologists observe the PPV in the process of translating texts from the Old Armenian language into New Armenian, after which he expresses the opinion that two parts of the PPG verbs should be preserved in the translation so that the stylistic side of this context does not suffer.
Keywords: Grabar; past participle; addition; definition; structure; verb tense; stylistic construction